Balance coordination: An important ability for young gymnasts - Ikonomi, E.; Bozaxhiu, A.; Puma, V.; Kosta, O. (Journal of Physical Education and Sport, 2025)
Background: Training in artistic gymnastics is a conscious and systematic process involving training loads, designed to develop various components such as movement skills, technical and tactical abilities, health and psychological, aspects. During the stages of sports training, the primary focus is on enhancing execution ability. Execution refers to the unity between the movement and its outcome, encompassing one or more motor actions performed within a specific timeframe, measurable through defined evaluation procedures. Balance defined as the ability to maintain postural control or equilibrium by managing the body's center of gravity within its base of support during any that involves shifting the center of gravity through muscular activity. Methods: In this study, were analyzed to balance test, eight young male gymnasts of Albanian national team, who are participants in gymnastics competitions at national level and 5 of them at international level. Measurements were made with same methodology in both periods. The tests were carried out in laboratory of Sports Scientific Research Center at Tirana Sports University. All the data obtained from performed tests were subjected to statistical processing, presenting average, standard deviation, variance, probability. Average (X) and coefficient of variance (CV) are calculated by ANOVA method according to general formula: = AVERAGE (Date). Standard deviation (SD) and probability (P) are calculated with EXEL 2019 method, with the general formula of EXEL = STDEV (Data). Significance was set to p<0.001 level. Results: In balance test B.T. for 10 seconds with eyes closed, four important parameters were measured in two test periods. Std. Ellipse Area cm² surface that describes P.C. during test, rel. Pathlength.mm/s, displacement speed P.C., abs. Pathlength.mm, length of path that describes P.C., EQ (AP) % balance result (equilibrium). Conclusions: Measuring balance gives us valuable information in programming muscle work. In artistic gymnastics, many element require this skill. For this reason, coach prioritizes this component during training. To our subjects conclude average level of balance.